STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DALAM PENINGKATAN PRODUKTIVITAS KARYAWAN INDUSTRI KULINER DI KABUPATEN JEMBER - Luckman Ashary (Growth, 2019)
The development of Creative Industry in Indonesia is increasing from year to year. Culinary Industry is one of the new creative activities, planned to be included in the creative industry sector by conducting a study on the mapping of processed food products typical of Jember regency which can be increased its competitiveness in the international retail and passar market. The study was conducted to collect data and information as much as possible about the processed food products typical of Jember District, to be disseminated through appropriate media, inside and outside the country, to gain competitive advantage in the modern retail market and international market. The importance of this activity is motivated that Jember Regency has a cultural heritage of typical food products, which is basically a source of comparative advantage for Indonesia. It's just that the lack of attention and management is interesting, making comparative advantage is not excavated into more economic value. Type of research used is survey research, that is research that take sample directly from population. Judging from the problems studied, this research is a descriptive research, which aims to provide a systematic description of scientific information derived from the subject or object of research. Descriptive research focuses on a systematic explanation of the facts obtained during the study (Sanusi, 2011). Population in this research is culinary industry entrepreneur in Jember Regency. In the survey the number of respondents who made the respondents is 25 culinary industry entrepreneurs in Jember regency. The sample is taken by purposive sampling with the criteria of culinary business entrepreneurs who have employees more than 5 people.